Forage-Yield and Nutrient Quality of New Brown Midrib (BMR) Mutant Lines of Sorghum - T. Wahyono; W. M. Indriatama; W. T. Sasongko; E. N. Shafira; T. F. Hidayat; S. Widodo; Y. Widiawati; M. N. Rofiq; Y. N. Anggraeny; A. Kurniawati; Dasumiati (Tropical Animal Science Journal, 2023)
The objective of this study was to evaluate the yield, nutrient profile and in vitro digestibility of new BMR mutant lines of sorghum in Indonesia. These mutant lines were GH2.1, GH2.2, GH2.3, GH4.1, GH4.2, GH4.3 and GH4.4. One sorghum mutant line (CTY) and two national sorghum varieties (Super 1 and Bioguma) were also evaluated as controls. In vitro digestibility and rumen fermentation were measured using Ankom Daisy Fermenter and Hohenheim gas test methods, respectively. In vitro measurement consisted of ten treatments with five replications following a completely randomized design. The highest stem sugar content was found in Bioguma (11.22%) and GH4.4 (9.32%) (p<0.05). The Bioguma variety and the GH2.3 mutant line had a higher number of stem segments and fresh forage yield than the Super 1 variety (p<0.05). A greater concentration of crude protein (CP) was observed for the GH.2.1, GH2.2, GH2.3 and GH4.1 lines (p<0.05). The GH2.3 mutant line had the lowest acid detergent lignin (ADL) content (p<0.05), while Bioguma had the highest level of non-fibre carbohydrate (NFC) compounds (p<0.05). The highest relative feed value (RFV) was observed for the GH2.3 line (p<0.05). Furthermore, GH4.2 and GH2.3 had greater in vitro true digestibility (IVTD) (p<0.05) but were not significantly different from Bioguma. Regarding yield characteristics, nutrient composition and in vitro digestibility values, the highest values were found in the Bioguma variety and the GH2.3 mutant line. Except for n-valerate (nC5), significant differences in all rumen fermentation parameters were observed among sorghum cultivars (p<0.05). Regarding the interrelationship between parameters, we found a medium correlation of DMD with the ADL and cellulose content of sorghum forage (R2 = -0.489 and R2 = -0.674, respectively). Based on these findings, the GH2.3 BMR mutant line should be further developed as forage sorghum.